Molecular Imaging of Abdominal Aortic Aneurysms - Brangsch, Julia; Reimann, Carolin; Collettini, Federico; Buchert, Ralf; Botnar, Rene M.; Makowski, Marcus R. (Trends in Molecular Medicine, 2017)
Abdominal aortic aneurysms (AAAs) represent a vascular disease with severe complications. AAAs are currently the overall 10th leading cause of death in western countries and their incidence is rising. Although different diagnostic techniques are currently available in clinical practice, including ultrasound (US), magnetic resonance imaging (MRI), and computed tomography (CT), imaging-based prediction of life-threatening complications such as aneurysm-rupture remains challenging. Molecular imaging provides a novel diagnostic approach for in vivo visualization of biological processes and pathological alterations at a cellular and molecular level. Its overall aim is to improve our understanding of disease pathogenesis and to facilitate novel diagnostic pathways. This review outlines recent preclinical and clinical developments in molecular MRI, positron emission tomography (PET), and single-photon emission computed tomography (SPECT) for imaging of AAAs.
CRIS-Team Scopus Importer:2023-03-08
Keywords: abdominal aortic aneurysm; magnetic resonance imaging; molecular imaging; positron emission tomography; single-photon emission computed tomography